E-Loyalty among millennials: Personal characteristics and social influences. (May 2019) - Purani, Keyoor; Kumar, Deepak S.; Sahadev, Sunil
Abstract: This study develops and validates a new, personal characteristics and peer influence based perspective on e-loyalty formation among millennial customers. Deviating from existing models, it examines the indirect influence of personal characteristics like perceived compatibility, innovativeness and peer influence in terms of perceived subjective norms. Data are collected from 380 millennial respondents from India who have made purchases from an e-retailer in the previous 6 months. The PLS-SEM model tests using Warp PLS 5.0 and the multiple mediation tests were done using PROCESS macro for SPSS 23.0. Embedded within the larger context of technology adoption, the findings suggest that personal characteristics and social influence play more crucial role in deciding the e-loyalty intentions of millennials. A better understanding of millennials' loyalty may help e-tailers in the development and implementation of effective marketing campaigns towards retaining them.